Ruang aktivitas perempuan dalam arsitektur vernakular Gunungsari, Tabanan, Bali - Winarta, I Wayan; Dharmadiatmika, I Made Agus (Jurnal Arsitektur Lansekap, 2018)
Space of women activities in vernacular architecture Gunungsari, Tabanan Bali. The space activities of women in the vernacular architecture of Bali has wider position compared with men. Women are given quite a lot of activities space than men, in addition to the ability to give birth and religious activity is high. This underlying pattern in the shape of space on the vernacular architecture of Bali, the Balinese traditional house building pattern that his philosophy is high, where the building is open and it functions more used for women's activities. The process of forming the concept of activity space of the woman, is the answer to the phenomenon of discrimination of women in architecture that is not always true. This research is useful for adding insight deep understanding of vernacular architecture, especially at the Division of spaces according to the person of its activities (gender), a traditional neighborhood development Setup for local residents and businesses for the development of the architectural patterns in rural settlements.